ANALISA UNSUR HARA MIKRO DARI FLY ASH LIMBAH INDUSTRI PULP DAN KERTAS - Maria Peratenta Sembiring; Chairul Chairul; Zulfansyah Zulfansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
The pulp and paper industry continues to grow and produces large amounts of fly ash waste from the biomass combustion process. Alternative waste management besides landfills needs to be developed so that the use of fly ash can be ecologically and economically acceptable, such as for land applications in industrial plantations, especially on peat soils. This paper presents the results of the analysis of micro nutrients from fly ash from pulp and paper mill waste that can be used for agriculture and forestry. The elemental content of boron (B) and zinc (Zn) can be detected in fly ash samples both by lauryl amine extraction and stearyl amine extraction, where the optimum amount is obtained using 15 gram of fatty amine and n-hexane solvent with a processing time of 4 hours. Stearyl amine gives a higher yield than lauryl amine because it has a longer saturated carbon chain.